2006
DOI: 10.2208/jsceseee.23.17s
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Ageing Behaviors of Rubbers Used for Bridge Bearings

Abstract: In order to evaluate the deterioration characteristics during the lifecycle of bridge rubber bearing, a series of long-term accelerated exposure tests are performed on four kinds of rubber materials widely utilized for bridge bearings. Different degradation factors are applied in these tests, such as thermal oxidation, ozone, low temperature ozone, ultraviolet radiation, salt water and acid rain. The test duration lasts from 96 hours to more than 6,000 hours. Mechanical properties of aged rubber specimens are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Deterioration of bearings is partially accounted for by reducing the area of the steel dowels using Equation 3. However, it has also been observed that elastomeric bearing pads undergo oxidation due to prolonged exposure (Itoh et al, 2006). Therefore, stiffness of the bearing pad (K = GA p /t p ; A p : area of pad; t p : thickness of pad) is updated with time in accordance with the results in Itoh & Gu (2009):…”
Section: Deterioration Mechanisms and Their Modelingmentioning
confidence: 85%
“…Deterioration of bearings is partially accounted for by reducing the area of the steel dowels using Equation 3. However, it has also been observed that elastomeric bearing pads undergo oxidation due to prolonged exposure (Itoh et al, 2006). Therefore, stiffness of the bearing pad (K = GA p /t p ; A p : area of pad; t p : thickness of pad) is updated with time in accordance with the results in Itoh & Gu (2009):…”
Section: Deterioration Mechanisms and Their Modelingmentioning
confidence: 85%
“…Environmental factors like oxygen exposure, heat, and sunlight, which deteriorate physical properties of rubber bearings such as elasticity and strength, are usually not considered during the design process of rubber bearings. Understanding the degradation of the material properties is considered essential in their lifetime prediction [1][2][3]. As the service temperature rises, molecular changes take place, resulting in a loss of mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative degradation is the most important factor that determines durability in most engineering applications, including bridge rubber bearings, where the oxygen availability is limited by diffusion [2][3]. Itoh, et al [3,7] have evaluated the evolution of tensile mechanical properties (such as elongation at break and tensile strength) of different types of rubber compounds used for bridge bearings exposed to different ageing tests, including thermal oxidation, ozone, low temperature ozone, ultraviolet radiation, salt water, and acid rain.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, these are intended to measure changes in the elastomer at the (elevated) service temperature or, secondly, these can be used as accelerated tests to estimate the degree of change, which would take place over much longer times at normal ambient temperature 1 . A series of accelerated exposure tests were performed by Itoh 2 , et al on various rubber materials including high damping rubber (HDR) to investigate the degradation due to different environmental factors. It was found that the thermal oxidation is the most predominant degradation factor affecting the HDR material.…”
Section: Introductionmentioning
confidence: 99%